Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome caused by first‐line antituberculosis drugs: Two case reports and a review of the literature. (22nd May 2019) - Coster, Alison; Aerts, Olivier; Herman, Anne; Marot, Liliane; Horst, Niels; Kenyon, Chris; Vlieghe, Erika; Hainaut, Philippe; Baeck, Marie
Abstract: Background: Patients suffering from drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome caused by first‐line antituberculosis drugs often need to be retreated rapidly. Patch tests prior to the reintroduction of antituberculosis drugs are rarely performed. Objectives: To highlight those drugs most often involved in DRESS caused by antituberculosis drugs, illustrate the potential value of patch tests to identify these culprit(s), and provide insights into how to rapidly retreat these patients. Methods: A detailed description of the work‐up of two illustrative patients, together with a literature review of similar cases, is provided. Results: All first‐line antituberculosis drugs may cause DRESS syndrome, but rifampicin and isoniazid are most frequently involved. Patch tests can be performed sooner than usually advised in the context of DRESS syndrome, and potentially with lower test concentrations, but false‐negative results are possible. Sequential reintroduction of patch test‐negative drugs is feasible, although the dose and order of drugs to be readministered, as well as the use of concomitant systemic corticosteroids, remain a matter of debate. Conclusion: Patch tests in the context of DRESS syndrome caused by antituberculosis drugs, despite their shortcomings, may potentially guide rapid retreatment of these patients.